2008
DOI: 10.2741/3009
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin as a target for cancer therapy

Abstract: Osteopontin (OPN) is a glycophosphoprotein cytokine that has multiple functions. OPN is expressed and secreted by various cells, and has a role in cell adhesion, chemotaxis, prevention of apoptosis, invasion, migration and anchorage-independent growth of tumor cells. Extensive research has demonstrated the pivotal participation of OPN in the regulation of cell signaling which controls neoplastic and malignant transformation. The elevated expression of OPN has been observed in a variety of cancers. OPN has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 95 publications
6
44
0
Order By: Relevance
“…OPNc could stimulate growth signal autonomy by different strategies, such as alteration of extracellular growth signals, of transcellular transducers of those signals or of intracellular circuits that translates those signals into action (26). Literature has provided evidence that total OPN affect the expression of genes involved in multiple aspects of tumor progression and malignant growth, including those involved on self-sufficiency in growth signals (42,43). In ovarian carcinoma, among all isoforms, OPNc could better stimulate these signals as compared with the remaining isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…OPNc could stimulate growth signal autonomy by different strategies, such as alteration of extracellular growth signals, of transcellular transducers of those signals or of intracellular circuits that translates those signals into action (26). Literature has provided evidence that total OPN affect the expression of genes involved in multiple aspects of tumor progression and malignant growth, including those involved on self-sufficiency in growth signals (42,43). In ovarian carcinoma, among all isoforms, OPNc could better stimulate these signals as compared with the remaining isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…3 There is mounting evidence that matricellular proteins play an important function in modulating cancer cell behavior and the tumor microenvironment. 4,5 Matricellular proteins are noncollagenous extracellular matrix proteins that function as modulators of cell behavior as well as regulators of matrix organization. 6 The matricellular proteins osteopontin [ In this issue of Cancer Biology & Therapy, Zhivkova-Galunska and coworkers examine the relative expression of osteopontin and osteonectin transcripts in a panel of 14 human pancreatic cancer cell lines, and determine whether there is any correlation between these RNA levels and characteristics associated with aggressive cancer phenotype.…”
mentioning
confidence: 99%
“…Cancer cells often maintain aggressive growth in an autocrine manner independent of external signals. OPN, as a growth factor-like, calcified ECMassociated protein, is secreted by cancer cells and in turn enhances their proliferation by binding with its receptor αvβ3 and/or CD44 [13,14], and then activating its downstream pathway, such as NF-kappa B-mediated pro-survival signaling [17]. Importantly, for the first time, we here demonstrated that overexpression of hOPN in the 293 cells significantly increases cell migration in vitro, as demonstrated by a transwell-based migration assay (P < 0.001, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…OPN therefore has the potential as a diagnostic and/or prognostic marker of metastases, and as an indicator of overall clinical outcome for many cancers, including osteosarcoma, and breast, lung and brain cancers [11,12]. As previously described, OPN acts as an autocrine growth factor to promote cell proliferation in a self-sufficient manner, and as a chemoattractant or a homing molecule to facilitate cancer metastasis to secondary sties [13,14]. To test the hypothesis that overexpression of OPN increases cell growth and motility in vitro, we expressed the recombinant human OPN (hOPN) gene in human embryo kidney-293 (293) cells.…”
Section: Introductionmentioning
confidence: 99%